FORMATION OF AN INNOVATIVE MECHANISM TO MINIMIZE FINANCIAL LOSSES OF OIL AND GAS PRODUCTION COMPANIES FROM THE CONSEQUENCES OF HYDROCARBON EMISSIONS - FADYEYEVA, Iryna; TUTS, Ilona (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article  reveals  the  essence  and s ubstantiates the  advantages  of  implementing  the proposed mechanism minimization of losses.. Environmental risks that arise in the process of functioning of oil and gas production enterprises and are accompanied by significant losses are identified. The problems of implementing economic and ecological mechanisms for minimizing losses from emissions in the context of environmental risk management have been identified. Proposals have been developed to provide compensation for losses of oil and gas production enterprises due to emissions of pollutants, as well as a model of the economic-ecological mechanism of minimizing losses as an effective way of managing environmental risks. In order to compensate environmental losses of oil and gas production enterprises, the use of mandatory environmental insurance is proposed. It is shown that the main directions of the development of the mandatory environmental insurance mechanism are the provision of real compensation for the insured environmental losses, the reduction of the burden on the state and local budgets, the development of economic bases for the analysis and management of environmental risks of oil and gas production enterprises.
Keywords: economic-ecological mechanism; loss minimization; hydrocarbon emissions; oil and gas production enterprises; mandatory environmental insurance